Mondor's disease of penis: a forgotten disease. Issue 6 (2nd December 2005) - Kumar, B; Narang, T; Radotra, B D; Gupta, S
Abstract : Background: Mondor's disease of penis is an uncommon genital condition involving the penile sulcus in a circumferential manner. Although this disorder is almost always self limited, it is associated with considerable psychological stress and sexual disharmony. Methods: All patients attending the sexually transmitted disease clinic during 1991–2003 were examined for evidence of Mondor's disease of penis. Detailed history and clinical findings were recorded in a specially designed proforma. Histopathological examination and staining with CD31 and CD34 monoclonal antibodies was also done in 11 patients. Results: 18 out of 1296 patients attending the sexually transmitted diseases (STD) clinic during the study period were found to have penile Mondor's disease, giving an incidence of 1.39%. 17 patients had history of one or more episodes of STDs. Histopathological specimens showed prominent vessels with plump endothelial cells and thickened blood vessel walls. The occasional vessel showed complete occlusion of its lumen. Conclusions: In our study we did not find any evidence of lymphatic involvement. Non-lymphatic vessels, mainly veins, were predominantly involved. In our opinion Mondor's phlebitis of penis or Mondor's disease of penis are better terms to describe the condition rather than non-venereal sclerosing lymphangitis.